Germinação de sementes de Bidens subalternans DC. em resposta a diferentes fatores ambientais - Pamplona, Juliana de Paiva (Universidade Federal Rural do Semi-Árido, 2018)
Bidens subalternans DC. is a weed very common in agricultural crops in whole Brazil. Its fixation is allowed by its high seed production and easy dispersal. Knowledge about factors influencing seed germination of this plant may contribute to develop management strategies. In this sense, this work aimed to assess seed germination of Bidens subalternans DC. as a function of different temperatures, photoperiod, soil depth, water deficit and saline stress. The experiments were accomplished in Seeds Analytical Laboratory from Universidade Federal Rural do Semi-Árido (UFERSA). The design was completely randomized with four repetitions. In all the experiments, we calculated daily germination of B. subalternans and data were analyzed using trust interval, at 5% probability. Results have shown germination rate higher than 77% in an alternate large temperature range (15/20° a 30/35 °C night/day). However, greatest germination and more consistent was registered at 25/30ºC night/day and only 11% of seeds germinated at 35/40°C night/day. In the presence of light (constant light and 12 hours of light/12 hours at darkness), germination was greater than 96%; in the lack of light, only 17% of seeds germinated. The need of light for the germination of these seeds was confirmed through the deepness of sowing experiment, in which the greatest rate (90%) was obtained using seeds put in soil surface. B. subalternans showed sensibility to water and saline stress and had its germination totally inhibited under water potential -0,4 MPa e -0,5 MPa, respectively. B. subalternans seeds showed high sensibility to high temperatures, water déficit and saline stress, suggesting that in areas with similar conditions its fixation is affected. The factors light and sowing deepness showed that seeds emitter (mechanical control) may be an efficient strategy for the management of B. subalternans
Germination of Bidens subalternans DC. seeds as a response to different environmental factors
Keywords: Picão-preto; Germinação; Defícit hídrico; Temperatura; Fotoblastismo; Beggartick; Germination; Water deficit; Temperature; Phtotoblastism; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA